5.2k views
3 votes
Which expressions are equivalent to the expression below? Check all that apply. x^-6/x^4=

A) x^-2
B) x^10
C) x^-10
D) x^-48
E) 1/x^10

User Zmt
by
5.5k points

2 Answers

1 vote

x^-6/x^4...first off move the x^-6 to the denominator to make it positive.

1/(x^6)(x^4)

when you multiply you add exponents

1/x^10

User Timfaber
by
5.9k points
6 votes

Answer:

  • C) x^-10
  • E) 1/x^10

Explanation:

The applicable rules of exponents are ...

x^-a = 1/x^a

(x^a)(x^b) = x^(a+b)

___

Using these rules, you have ...


(x^(-6))/(x^4)=(x^(-6))(x^(-4))=x^(-6-4)\\\\=x^(-10)=(1)/(x^(10))

These forms match choices C and E.

User Felicha
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.